Detection of herpes viruses in the cerebrospinal fluid of adults with suspected viral meningitis in Malawi - Benjamin, Laura A.; Kelly, M.; Cohen, D.; Neuhann, Florian; Galbraith, S.; Mallewa, M.; Hopkins, M.; Hart, I. J.; Guiver, M.; Lalloo, D. G.; Heyderman, R. S.; Solomon, T. (Infection, 2013)
We looked for herpes simplex virus types 1 and 2 (HSV-1 and HSV-2, respectively), varicella zoster virus (VZV), Epstein-Barr virus (EBV) and cytomegalovirus (CMV) DNA in Malawian adults with clinically suspected meningitis.
Published online: 14 July 2012
Gesehen am 23.11.2020